2012
DOI: 10.1039/c1sc00556a
|View full text |Cite
|
Sign up to set email alerts
|

A general approach to the enantioselective α-oxidation of aldehydesvia synergistic catalysis

Abstract: A new enantioselective α-oxidation of aldehydes has been accomplished using TEMPO and a synergistic combination of copper and organic catalysis. Expanding upon recently reported mechanistic studies, these mild catalytic conditions provide stable aldehyde products bearing a wide array of electronically and sterically diverse substructures. The utility of these oxidized products is highlighted by subsequent derivatization to a variety of common chiral synthons, without loss in enantiopurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…Recently, through mechanistic studies performed in the MacMillan group this mechanism was shown to be incorrect; the transformation most likely proceeds via synergistic catalysis wherein the FeCl 3 coordinates to TEMPO, creating a complex that is electrophilic at oxygen and therefore activated towards enamine addition. 21 Based on this mechanistic insight, MacMillan and coworkers improved this transformation by switching to CuCl 2 (known to form stable complexes with TEMPO) and using amine catalyst 53 . This broadened the functional group tolerance of the reaction and increased both yield and enantioselectivity (Scheme 15).…”
Section: Carbonyl α-Functionalizationmentioning
confidence: 99%
“…Recently, through mechanistic studies performed in the MacMillan group this mechanism was shown to be incorrect; the transformation most likely proceeds via synergistic catalysis wherein the FeCl 3 coordinates to TEMPO, creating a complex that is electrophilic at oxygen and therefore activated towards enamine addition. 21 Based on this mechanistic insight, MacMillan and coworkers improved this transformation by switching to CuCl 2 (known to form stable complexes with TEMPO) and using amine catalyst 53 . This broadened the functional group tolerance of the reaction and increased both yield and enantioselectivity (Scheme 15).…”
Section: Carbonyl α-Functionalizationmentioning
confidence: 99%
“…Catalytic amounts of copper(II) chloride gave a similar complex with TEMPO, and broadened the scope to several functionalized aliphatic aldehydes with enantiomeric excesses up to 95%. 102 This method was extended to the use of resin-bound peptides instead of chiral imidazolidinones, used FeCl 2 Á 4H 2 O as second catalyst and took place in aqueous media. 103 The procedure became even greener with air as oxidant and the enzyme laccase as cocatalyst instead of FeCl 2 .…”
Section: Aminoxylations With Tempomentioning
confidence: 99%
“…The present vanadium-lanthanum dual catalytic approachi s tolerant of readily enolizable aldehydes containing b,g-unsaturation formed in situ;a lso represents an ew general approach for the formation of aldol products.W hile most of the cases at present were best performed with excess epoxide, in several instances 1.2-1.5 equivalents gave good results. Indeed, it should be noted that the use of excess acceptor aldehyde in the aldol reaction is common.A tp resent time, the d.r.i sa pproximately 80:20, which constitutes as ignificant improvement compared to the traditional use of lithium enolates addingt oaldehydesa si llustrated in Equation (1).…”
mentioning
confidence: 98%
“…Contemporaneousd ual catalysis expands on this traditional use of catalysis by allowingf or thes imultaneous in situ activation of both coupling partnerso fareaction through the use of two distinct catalysts. [1] The resulting two catalyst-activated intermediates are coupled with one another in preference over reactivity with stoichiometric amountso f unactivated substrates present in the reaction flask. Use of this type of dual catalysis has resultedi nt he disclosure of novel reactivities as well as products that have been difficult to obtain under traditional one-catalyst approaches.…”
mentioning
confidence: 99%